2015
DOI: 10.1080/17461391.2015.1103317
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic response following high‐intensity running work‐to‐rest interval manipulation

Abstract: The cardiorespiratory, cardiac autonomic (via heart rate variability (HRV)) and plasma volume responses to varying sequences of high-intensity interval training (HIT) of consistent external work were investigated. Twelve moderately trained males underwent three HIT bouts and one control session. The HIT trials consisted of warm-up, followed by 12 min of 15 s, 30 s or 60 s work:relief HIT sequences at an exercise intensity of 100% of the individual velocity at [Formula: see text]O2max (v[Formula: see text]O2max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
(61 reference statements)
3
16
0
2
Order By: Relevance
“…However, the 30/30 protocol elicited the least IL-6 and Mb response while the inter-trial differences in all other analysed variables were negligible. These findings support the previously published results demonstrating the least disruption of the cardiac autonomic regulation caused by the 30/30 protocol when compared to 15/15 and 60/60 protocols (Cipryan et al, 2016). …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the 30/30 protocol elicited the least IL-6 and Mb response while the inter-trial differences in all other analysed variables were negligible. These findings support the previously published results demonstrating the least disruption of the cardiac autonomic regulation caused by the 30/30 protocol when compared to 15/15 and 60/60 protocols (Cipryan et al, 2016). …”
Section: Discussionsupporting
confidence: 93%
“…Since the beneficial effect of IL-6 on the muscle metabolism had been shown (Raschke and Eckel, 2013), our results indicated that the 15/15 and 60/60 protocols might be preferred to the 30/30 protocols in order to maximize the training stimulus. These findings are in conformity with the sister paper, which showed a similar acute cardiorespiratory response to all three HIIT protocols as well as the least disturbance of cardiac autonomic regulation following the 30/30 HIIT protocol (Cipryan et al, 2016). …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations